Effects of Short-Term Dynamic Balance Training on Postural Stability in School-Aged Football Players and Gymnasts - Kenville, Rouven; Maudrich, Tom; Körner, Sophie; Zimmer, Johannes; Ragert, Patrick (Frontiers in Psychology, 2021)
Static and dynamic balance abilities enable simple and complex movements and are determinants of top athletic performance. Balance abilities and their proficiency differ fundamentally with respect to age, gender, type of balance intervention and type of sport. With this study, we aimed at investigating whether 4 weeks of dynamic balance training (DBT) improves static balance performance in school-aged gymnasts and football players. For this purpose, young male gymnasts (n = 21) and male football players (n = 20) completed an initial static balance assessment consisting of two one-legged stance (left & right foot) and two two-legged stance (eyes open & eyes closed) tasks. Subsequently, all participants underwent a 4-week intervention. DBT consisting of 9 individual tasks was performed 2 times per week. Another static balance assessment followed 1 day after the last training session and retention was assessed 2 weeks later. Dynamic balance scores and total path length were analyzed via rank-based repeated measures design using ANOVA-type statistics. The influence of factors GROUP and TIME on the static and dynamic balance performance was examined. Prior to DBT, young gymnasts showed better static balance performance than football players. However, after intervention, both groups improved in both one-legged stance tasks and also had high retention rates in these tasks. No significant improvements were seen in either group in the two-legged balance tests. Both groups improved in the dynamic balance tasks, although no differences in learning rates were evident. Our findings imply an inter-relationship between both static and dynamic balance components. Consequently, training regimes should include both balance components to facilitate early development of balance ability.